2012
DOI: 10.1021/om300622c
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of the Gilman Reagent with Double Bonds across the π–σ Continuum

Abstract: By using rapid injection NMR at low temperatures, a variety of π-complexes of lithium dimethylcuprate(I) with C−C, C− N, and C−S double bonds have been prepared and characterized. Complexation is generally accompanied by large upfield changes in chemical shift for the substrate carbon atoms bonded to copper. In the case of α,β-unsaturated carbonyl compounds, the changes for the carbonyl carbons are much smaller in magnitude, which is consistent with the usual η 2 representation of these structures. It is possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…Organocuprates form p-complexes with activated alkenes and alkynes, [1][2][3] which are well-characterized intermediates, thanks to mechanistic studies on the conjugate addition reactions of these useful reagents. 4,5 We were able to extend our preparations of cuprate p-complexes from C-C to C-N double bonds by using isothiocyanates and azachalcones. 4 In an attempt to extend our studies to C-N triple bond complexes, we investigated acyl cyanides and serendipitously discovered the title compounds.…”
mentioning
confidence: 99%
“…Organocuprates form p-complexes with activated alkenes and alkynes, [1][2][3] which are well-characterized intermediates, thanks to mechanistic studies on the conjugate addition reactions of these useful reagents. 4,5 We were able to extend our preparations of cuprate p-complexes from C-C to C-N double bonds by using isothiocyanates and azachalcones. 4 In an attempt to extend our studies to C-N triple bond complexes, we investigated acyl cyanides and serendipitously discovered the title compounds.…”
mentioning
confidence: 99%
“…Presumably, they are less important for the addition to the corresponding nitriles because nitrogen has a lower Li + affinity than oxygen . However, adducts stable at room temperature are predicted to form only if at least two cyano groups are attached to the carbon–carbon double bond of the Michael acceptor, in line with previous NMR spectroscopic experiments …”
Section: Discussionmentioning
confidence: 99%
“…[11] Preparation of NMR samples has been described. [10,16] For details of the molecular weight measurements, see the Supporting Information. Reference compounds (internal standards) [21] for these diffusion-ordered NMR studies are shown below: CCDC-928158 (1) contains the supplementary crystallographic data for this paper.…”
Section: Methodsmentioning
confidence: 99%
“…ORTEP plot (50 % ellipsoids) for 1. Selected bond distances [] and angles [8]: CuÀC, 1.914(3); CuÀS, 2.1797 (7); LiÀS, 2.431(4); LiÀO1, 1.920 (5); LiÀO2, 1.914 (5); LiÀO3, 1.914(4); CÀCuÀS, 176.15 (12); CuÀSÀLi, 98.94 (10).…”
mentioning
confidence: 99%